THE EFFECT OF CUSTOMER SATISFACTION AND BRAND EQUITY ON THE INTEREST IN REPURCHASING SUGAR - Ringgo Ismoyo Buwono; Garnet Filemon; Tri Wisudawati; Wahyu Adhi Saputro (Universitas Airlangga, 2021)
Currently, the consumer goods business in Indonesia is very strict, including for sugar products. Until now, sugar products cannot be fully replaced by other products. The purpose of this study was to determine the effect of customer satisfaction and brand equity on the interest in repurchasing sugar products. This study used a descriptive analytic method using two data sources, namely primary data and secondary data. Primary data obtained by interviewing consumers who consume sugar as many as 60 people. Secondary data obtained from data sourced on the internet, books, journals and other sources deemed relevant. Analysis of the data used in this study is multiple linear regression with the dependent variable repurchase interest and two independent variables, namely customer satisfaction and brand equity. Based on the research results, it is known that the significance value of the F test is 0.000 so that the value is less than 5% alpha. Thus it can be said together that the variables of customer satisfaction and brand equity have an effect on the interest in repurchasing sugar. Based on the results of the t-test, it can be seen that the variable X1 (customer satisfaction) has a significance value of 0.0007 so that the value is less than alpha 0.05 in other words that the variable X1 (customer satisfaction) affects the interest in repurchasing. Variable X2 (brand equity) has a significance value of 0.0317 so that the value is less than alpha 0.05, in other words that the X2 variable (brand equity) affects the dependent variable repurchase interest.